A A Comparison of Economics and Attractiveness of Fiscal System in Several Southeast Asian Countries : A Case Study of Three Oil And Gas Field in Indonesia - Gabriela Martines Martines; Dwi Atty Mardiana; Pri Agung Rakhmanto (Journal of Earth Energy Science, Engineering, and Technology, 2023)
The implementation of fiscal terms in the upstream oil and gas industry in a country is carried out with the hope of accelerating the decision-making process and making the attractiveness of upstream oil and gas investment more attractive to investors. This study evaluates fiscal terms in a country in a region used in Indonesia, Malaysia, Thailand, and Vietnam to determine the attractiveness of the fiscal terms. Using several indicators of government take (GT), front loading index (FLI), and composite score (CS), the fiscal attractiveness ranking of five fiscal schemes will be analyzed so that investors can consider which fiscal scheme is most attractive for their investment. The results of the economic analysis based on the economic indicators of IRR, NPV, POT, and PI show that the newly developed onshore, existing onshore, and offshore gas fields are included in the investment feasibility criteria with attractive economic values when applied with all fiscal schemes. While the ranking results with GT, FLI, and CS indicators show that Indonesia's gross split PSC has an attractive attractiveness when applied to newly developed onshore fields, R/C PSC on existing onshore fields, and Thailand’s concessions on offshore gas fields.